National-Language Orientation in Teaching The Russian Language to Foreign Students at a Medical University - Mamedova Kamila; Razykova Lola Tuychievna (Journal of Higher Education and Academic Advancement, 2024)
The article deals with the problem of intensifying the process of teaching foreign students the Russian language at the pre-university stage through the use of a nationally oriented methodology for teaching Russian as a foreign language, relying on the native language as a way to improve the quality of teaching the Russian language.